2012
DOI: 10.1103/physrevlett.109.147404
|View full text |Cite
|
Sign up to set email alerts
|

Visible-to-Telecom Quantum Frequency Conversion of Light from a Single Quantum Emitter

Abstract: We demonstrate efficient (>30%) quantum frequency conversion of visible single photons (711 nm) emitted by a quantum dot to a telecom wavelength (1313 nm). Analysis of the first- and second-order coherence before and after wavelength conversion clearly proves that pivotal properties, such as the coherence time and photon antibunching, are fully conserved during the frequency translation process. Our findings underline the great potential of single photon sources on demand in combination with quantum frequency … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
213
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 268 publications
(224 citation statements)
references
References 40 publications
4
213
0
Order By: Relevance
“…Telecom frequency conversion of photons connected to several examples of quantum matter has recently been demonstrated, including quantum dots [21][22][23][24], cold gas atomic ensembles [25][26][27] and solid-state ensembles [28]. Applying QFC to trapped ions is challenging.…”
mentioning
confidence: 99%
“…Telecom frequency conversion of photons connected to several examples of quantum matter has recently been demonstrated, including quantum dots [21][22][23][24], cold gas atomic ensembles [25][26][27] and solid-state ensembles [28]. Applying QFC to trapped ions is challenging.…”
mentioning
confidence: 99%
“…To this end, bridging the gap between low loss telecom wavelengths for long-range communication and the atomic wavelengths quantum frequency conversion (QFC) is necessary [14][15][16]. In the present experiment we produce frequency-degenerate photon pairs, generated by spontaneous parametric down conversion (SPDC), resonant with an atomic transition of 40 Ca + at 854 nm.…”
Section: Introductionmentioning
confidence: 99%
“…One photon serves as a herald, which is detected by a silicon avalanche photon detector (Si-APD, Perkin Elmer SPCM-AQR-14, 30 % detection efficiency at 854 nm), while its partner photon is sent to the frequency converter setup. For frequency conversion we make use of difference frequency generation in a periodically poled lithium niobate ridge waveguide (similar to the device described in [15]). The conversion from λ s = 854 nm to the telecommunications Oband around λ i = 1310 nm is stimulated by a strong coherent pump field at a wavelength of λ p = 2453 nm (1/λ s − 1/λ p = 1/λ i ).…”
Section: Quantum and Classical Channel In A Single Fibermentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the large radiative and nonradiative losses of the plasmon [15][16][17] , it is difficult to efficiently excite nanomaterials by weak light. If the losses in the antenna are successfully suppressed, we can expect the antenna-assisted system to be applied to key technologies in quantum information, communication and computation such as visible-totelecom frequency conversion of single photons emitted by a quantum dot 18 and single-photon switch 19,20 . In the previous work, we theoretically demonstrated optical linear responses on a antenna-molecule coupled system and reported that the molecule efficiently absorbs the incident light energy with the loss in the antenna suppressed.…”
Section: Introductionmentioning
confidence: 99%